Assessing the impact of a school‐based latrine cleaning and handwashing program on pupil absence in Nyanza Province, Kenya: a cluster‐randomized trial. Issue 10 (24th July 2014) - Caruso, Bethany A.; Freeman, Matthew C.; Garn, Joshua V.; Dreibelbis, Robert; Saboori, Shadi; Muga, Richard; Rheingans, Richard
Abstract Objectives Improving school water, sanitation and hygiene (WASH) conditions reduces pupil absence and illness. However, these benefits may depend on the conditions of the latrines and availability of consumables. We sought to determine whether a low‐cost, policy‐relevant, environmental‐level latrine cleaning intervention could improve latrine cleanliness, increase its use and reduce absenteeism. Methods In a three‐arm, cluster‐randomized trial we assessed absence via periodical roll‐call among 17 564 pupils in 60 schools that had previously received WASH improvements as part of the SWASH+ project. Latrine conditions and use were also assessed using structured observation. Latrine cleanliness increased significantly during the post‐intervention period among schools receiving the latrine cleaning package compared to controls, as did handwashing with soap. We found no difference in latrine use and absence across arms. Conclusions The additive impact of cleaning may not have been strong enough to impact absence above and beyond reductions attributable to the original WASH infrastructure improvements and basic hygiene education the schools previously received. Improving latrine conditions is important for the dignity and well‐being of pupils, and investments and strategies are necessary to ensure that school toilets are clean and pupil‐friendly.